Scholar Entangled: The Unattainable Detachment in Social Inquiry - Kasputis, Juozas (Problemos, 2021)
The practice of social studies continues to be a complicated scientific endeavor. From an epistemological point of view, the social sciences, unlike the natural sciences, do not conform to the predominant definition of science. The existing differences among expositions of “science,” “inquiry,” and “studies” lie with the contested role of the intellectual who is embarked on understanding the social realm. The “maturity” of the social sciences is usually discussed in the context of objectivity and rationality. But continuing epistemological debates would be insufficient without reference to the scholar as a human studying humans. The philosophy of science has focused mainly on the procedures of knowledge accumulation, neglecting social context and its implications for inquiry. To address this neglect, this essay sets out first to retrace doubts about the role of the scholar that emerged with the institutionalization of the social sciences at the outset of the twentieth century and then to rethink these issues in terms of recent scientific developments. What surfaces is a new, participatory role for scholars that demands responsible contextualization and a broader conception of causal stories.